A systematic review of variables used to assess clinically acceptable alignment of unilateral transtibial amputees in the literature. (August 2018) - Tafti, Nahid; Hemmati, Fatemeh; Safari, Reza; Karimi, Mohammad Taghi; Farmani, Farzad; Khalaf, Ali; Mardani, Mohammad Ali
Prosthetic alignment is a subjective concept which lacks reliability. The outcome responsiveness to prosthetic alignment quality could help to improve subjective and instrument assisted prosthetic alignment. This study was aimed to review variables used to assess clinically acceptable alignment in the literature. The search was done in some databases including: Google Scholar, PubMed, EBSCO, EMBASE, ISI Web of Knowledge and Scopus. The first selection criterion was based on abstracts and titles to address the research questions of interest. The American Academy of Orthotics and Prosthetics checklists were used for paper risk of bias assessment. A total of 25 studies were included in this study. Twenty-four studies revealed the critics of standing position or walking to locate clinically acceptable alignment, only one study measured outcomes in both situations. A total of 253 adults with transtibial amputations and mean age of 48.71 years participated in included studies. The confidence level of included studies was low to moderate, and before–after trial was the most common study design (n = 19). The joint angle, load line location with respect to joints and center of pressure–related parameters were reported as sensitive outcomes to prosthetic alignment quality in standing posture. The amount of forces at various parts of gait cycle and time of events were sensitive to prosthetic alignment quality during walking. Standing balance and posture and temporal parameters of walking could help to locate clinically acceptable alignment.